Determination of DNA sequences required for regulated Mycobacterium tuberculosis RecA expression in response to DNA-damaging agents suggests that two modes of regulation exist. - Movahedzadeh, F (1997)
The recA gene of Mycobacterium tuberculosis has previously been cloned and sequenced (E. O. Davis, S. G. Sedgwick, and M. J. Colston, J. Bacteriol. 173:5653-5662, 1991). In this study, the expression of this gene was shown to be inducible in response to various DNA-damaging agents by using a transcriptional fusion to the reporter gene encoding chloramphenicol acetyltransferase. A segment of DNA around 300 bp upstream of the coding region was shown to be required for expression. However, primer extension analysis indicated that the transcriptional start sites were 47 and 93 bp upstream of the translation initiation codon. Sequence motifs with homology to two families of Escherichia coli promoters but also with significant differences were located near these proposed transcription start sites. The differences from the E. coli consensus patterns would explain the previously described lack of expression of the M. tuberculosis recA gene from its own promoter in E. coli. In addition, the M. tuberculosis LexA protein was shown to bind specifically to a sequence, GAAC-N4-GTTC, overlapping one of these putative promoters and homologous to the Bacillus subtilis Cheo box involved in the regulation of SOS genes. The region of DNA 300 bp upstream of the recA gene was shown not to contain a promoter, suggesting that it functions as an upstream activator sequence.